Impact of Staphylococcus aureus regulatory mutations that modulate biofilm formation in the USA300 strain LAC on virulence in a murine bacteremia model. Issue 8 (17th November 2017) - Rom, Joseph S.; Atwood, Danielle N.; Beenken, Karen E.; Meeker, Daniel G.; Loughran, Allister J.; Spencer, Horace J.; Lantz, Tamara L.; Smeltzer, Mark S.
ABSTRACT: Staphylococcus aureus causes acute and chronic forms of infection, the latter often associated with formation of a biofilm. It has previously been demonstrated that mutation of atl, codY, rot, sarA, and sigB limits biofilm formation in the USA300 strain LAC while mutation of agr, fur, and mgrA has the opposite effect. Here we used a murine sepsis model to assess the impact of these same loci in acute infection. Mutation of agr, atl, and fur had no impact on virulence, while mutation of mgrA and rot increased virulence. In contrast, mutation of codY, sarA, and sigB significantly attenuated virulence. Mutation of sigB resulted in reduced accumulation of AgrA and SarA, while mutation of sarA resulted in reduced accumulation of AgrA, but this cannot account for the reduced virulence of sarA or sigB mutants because the isogenic agr mutant was not attenuated. Indeed, as assessed by accumulation of alpha toxin and protein A, all of the mutants we examined exhibited unique phenotypes by comparison to an agr mutant and to each other. Attenuation of the sarA, sigB and codY mutants was correlated with increased production of extracellular proteases and global changes in extracellular protein profiles. These results suggest that the inability to repress the production of extracellular proteases plays a key role in attenuating the virulence of S. aureus in acute as well as chronic, biofilm-associated infections, thus opening up the possibility that strategies aimed at the de-repression of protease production could be used to broad therapeutic advantage. They also suggest that the impact of codY, sarA, and sigB on protease production occurs via an agr -independent mechanism.